Accumulation of economic hardship and health during the COVID-19 pandemic: Social causation or selection?. (April 2021) - Bierman, Alex; Upenieks, Laura; Glavin, Paul; Schieman, Scott
Abstract: This study examines whether economic hardship during the COVID-19 pandemic is deleteriously associated with psychological distress and self-rated health. A social causation perspective suggests that exposure to economic hardship will harm well-being, but a social selection perspective suggests that the appearance of health effects of hardship during the pandemic are attributable to the increased risk of exposure to hardship associated with poor well-being at the start of the pandemic. We also propose a third perspective, economic selection, which suggests that economic hardship prior to the pandemic negatively affects health and increases risk of exposure to hardship during the pandemic; consequently, an association between health and economic hardship during the pandemic may be spurious, and entirely due to pre-existing levels of hardship. To test these competing perspectives, we use a longitudinal study based in Canada that began in late March of 2020 and followed respondents monthly in April, May, and June. Baseline psychological distress and self-rated health, as well as economic hardship prior to the pandemic, independently predict the accumulation of monthly periods of hardship from April to June. The accumulation of periods of hardship from April to June is deleteriously associated with psychological distress and self-rated health in June. Controls for prior economic hardship and baseline health weaken the association between accumulation of periods of hardship and psychological distress, while also eliminating the association between accumulation of hardship and self-rated health. These findings favor a social causation perspective for psychological distress and a social selection perspective for self-rated health, with less evidence found in support of economic selection. This study took place during the first months of the COVID-19 pandemic, though, and associations with self-rated health may have become more evident as hardship further wore on individual well-being over a longer period of time. Highlights: Psychological distress in March 2020 predicted more hardship between April and June. Worse self-rated health (SRH) in March predicted consistent hardship from April–June. These associations were independent of hardship prior to the pandemic. Hardships from April–June were associated with more distress and worse SRH in June. Baseline health controls negated hardship's links with June SRH but not distress.